The Prophet, the Speech and the Circulation of Pentecostal Charisma - Campos, Roberta Bivar Carneiro (Revista de Antropologia, 2012)
The phenomenon of transformation of the prophet into a celebrity of faith leads us to reflect up on the ways of transmission and routinization of charisma within pentecostal context. This article aims to address the authority of charismatic Pentecostal leaders in the Brazilian context, how the charisma circulates and is transmitted. Three directions in which the charisma flows are highlighted: 1. its commodification as it happens through paid courses, making it clear that one can learn to be a leader with his own charismatic leaders, 2. the charisma as well, besides being apprehended in a commercial and public space, is passed as symbolic capital through the family names of the charismatic leader, like the families Valadão, Soares, Malafaia, and others 3. In order the authority of charisma to be established there is the need it to be collectively spread between pastors and the faithful. The later, in turn, also mimic the leader’s charisma, accessing the capital and getting the charismatic habitus not only through participation in worship but also by the consumption of media products in general. To follow the charisma flow is also to follow the ways the Pentecostal message globalizes.